An experimental and numerical investigation of using palm oil fuel ash as a partial cement replacement in steel fiber-reinforced concrete - Hasan, Kamrul; Roy, Swaranjit; Fadzil, Mat Yahaya (Springer, 2024)
Due to rapid population growth and expansion of the construction industry, cement consumes significant amounts of natural resources and releases harmful pollutants such as carbon dioxide () into the atmosphere. The production of cement generates nearly 10% of the total worldwide emissions each year. Therefore, using palm oil fuel ash (POFA), an agricultural by-product of burning waste materials such as palm kernel shells, palm oil fibers, and palm oil shells, as a semi-substitute for cement will help to minimize the dependency on cement and reduce the greenhouse effect and environmental pollution. In this regard, to examine the overall performance of steel fiber-reinforced concrete (SFRC) containing 0–30% POFA as a partial cement replacement, this article aimed to investigate POFA’s physical and chemical properties, morphological characteristics, and both the experimental and numerical performance of the fresh, hardened, and durable properties of the SFRC. The workability, compressive strength, drying shrinkage, and heat of hydration test were performed and analyzed. The result demonstrated that adding POFA reduced concrete workability and drying shrinkage, and the hydration heat initially increased, but it decreased after reaching a 30% POFA replacement level. On the other hand, the POFA particles significantly improve the compressive strength up to a replacement level of 20%. Consequently, the outcome suggests that using POFA in SFRC as a cement partial replacement could produce sustainable green building materials that would reduce emissions and create low-cost cementitious materials.